MENINGKATKAN MOTIVASI BELAJAR SISWA MELALUI BIMBINGAN BELAJAR DARING DI TENJO - Kurnia Putri Sepdikasari Dirgantoro; Pitaya Rahmadi; Tanti Listiani; Ernie Bertha Nababan (Universitas Pelita Harapan, 2022)
Pandemic conditions are continuing and have an impact on learning. Under such conditions, perhaps students are already familiar with distance learning and adapt to those conditions. However, it is undeniable that not all children can still have good motivation during online learning. Student learning motivation must still be moved so that students' enthusiasm for learning continues to be encouraged and can follow the learning. Although there are already several schools that implement Limited Face-to-Face Learning (PTMT), students still need assistance, for example during independent study hours in developing their knowledge. Especially children of Junior High School (SMP) and High School (SMA) or Vocational High School (SMK) age 7, 8, 9, 10, and 11 are in the adolescent stage that requires attention so that they can focus on learning. One of the things that can be done to give real attention is to accompany them to study outside of school hours. Tenjo tutoring in collaboration with GKI Gading Serpong is here to answer these problems. The goal is to provide services that directly impact the needs of junior high and high school / vocational school students, especially in encouraging student learning motivation. This tutoring activity is carried out online. After being implemented for 5 months, the student's learning motivation score did not appear to have increased significantly. However, based on open-ended questions, 92% of students stated that they became enthusiastic about learning when taking this tutoring.abstract in BahasaKondisi pandemi masih terus berlanjut dan berdampak terhadap pembelajaran. Dalam kondisi demikian, mungkin siswa sudah terbiasa dengan pembelajaran jarak jauh dan beradaptasi dengan kondisi tersebut. Namun tidak dapat dipungkiri bahwa tidak semua anak bisa tetap memiliki motivasi yang baik selama pembelajaran daring. Motivasi belajar siswa harus tetap digerakkan sehingga semangat belajar siswa terus terpacu dan dapat mengikuti pembelajaran. Meski sudah ada beberapa sekolah yang melaksanakan Pembelajaran Tatap Muka Terbatas (PTMT), siswa tetap memerlukan pendampingan misalnya pada saat jam belajar mandiri dalam mengembangkan pengetahuannya. Khususnya anak usia Sekolah Menengah Pertama (SMP) dan Sekolah Menengah Atas (SMA) atau Sekolah Menengah Kejuruan (SMK) kelas 7, 8, 9, 10, dan 11 berada di tahap remaja yang membutuhkan perhatian sehingga mereka bisa fokus dalam pembelajaran. Salah satu yang bisa dilakukan untuk memberikan perhatian yang nyata adalah mendampingi mereka belajar di luar jam sekolah. Bimbingan belajar Tenjo bekerja sama dengan GKI Gading Serpong hadir untuk menjawab permasalahan tersebut. Tujuannya adalah menghadirkan pelayanan yang langsung berdampak bagi kebutuhan siswa SMP dan SMA/SMK khususnya dalam mendorong motivasi belajar siswa. Kegiatan bimbingan belajar ini dilaksanakan secara daring. Setelah dilaksanakan selama 5 bulan, secara skor motivasi belajar siswa tidak terlihat mengalami peningkatan secara signifikan. Namun berdasarkan pertanyaan terbuka, 92% siswa menyatakan menjadi semangat belajar ketika mengikuti bimbingan belajar ini.